Revision and an empirical evaluation of the Chinese Patient Health Literacy Scale - Ying CHEN; Jian DONG; Xiang-yang TIAN (Editorial Office of Chinese Journal of Public Health, 2022)
Objective To modify the Chinese Patient Health Literacy Scale (CPHLS) for improving the reliability and validity of the scale. Methods From January to May 2021, the CPHLS was preliminarily revised by expert consultation and the revised electronic scale was employed to measure the health literacy of 2 808 outpatients randomly selected at 14 hospitals in eastern, central and western China. SPSS 23.0 was utilized for Cronbach's α calculation and exploratory factor analysis (EFA) to further improve the revised scale; AMOS 23.0 was applied to build a structural equation model (SEM) to test the validity of the scale. Results The Cronbach's α coefficient of the preliminarily revised CPHLS was 0.841 and the α coefficients of the scale's five dimensions were 0.751 for concept of medical science, 0.787 for disease self-management skills, 0.568 for medical common sense, 0.725 for self-efficacy , and 0.412 for medical information cognition, respectively, with an overall cumulative proportion of variance of 62.538%. Three common factors of the revised scale (e.g. self-efficacy, disease self-management skills and medical common sense) were extracted according to the results of EFA. After deleting four original items, the α coefficient of the revised scale was raised to 0.845, the α coefficients of the three dimensions were 0.926, 0.831, and 0.753 and the cumulative proportion of variance was 67.228%. The SEM analysis on the revised scale demonstrated that the dimension-specific factor load capability ranged 0.53 - 0.90 and the constructed SEM is of good overall goodness of fit, with the root mean square residual (RMR) of 0.083, root mean square error of approximation (RMSEA) of 0.086, goodness-of-fit index (GFI) of 0.926, adjusted goodness-of-fit index (AGFI) of 0.891, normed fit index (NFI) of 0.928, relative fit index (RFI) of 0.909, incremental fit index (IFI) of 0.931, the Tacker-Lewis index/non-normed fit index (TLI/NNFI) of 0.913, comparative fit index (CFI) of 0.931, parsimony goodness-of-fit index (PGFI) of 0.631, parsimony-adjusted normed fit index (PNFI) of 0.737, parsimony-adjusted comparative fit index (PCFI) of 0.740, and the critical number (CN) of 171, respectively. Conclusion The revised Chinese Patient Health Literacy Scale is of good internal consistency reliability and construct validity, indicating a potential application in the evaluation on patients' health literacy.